A study of menstrual hygiene management in urban and rural adolescent girls in Ambala (Haryana) - Garg, Shallu; Bhardwaj, Anu; Mittal, Anshu; Bhonsla, Suresh (Indian Journal of Community Health, 2020)
Background: Adolescent girls often lack knowledge regarding reproductive health including menstruation hygiene. Poor menstrual hygiene can be a precursor reproductive tract infections and even cancer cervix. Objectives: To study the menstrual hygiene management among rural and urban school going adolescent girls Material and Methods: A community based cross sectional study was conducted among 420 adolescent girls (10 - 19 years). A self-designed semi- structured questionnaire was used to study the knowledge and practise regarding menstrual hygiene. Results: Knowledge about menstruation before attainment of menarche was 69% in urban and 58.9% in rural. Mother was the main source of information. Still 23.6% girls were using cloth or towels as menstrual absorbent, and 26.6% girls in rural area were washing their menstrual absorbent to be reused.91.7% and 81% girls had some restriction during menstruation Conclusion: Awareness in urban adolescent girls was more in comparison to rural girls. The usage of sanitary pads was similar in both rural and urban areas. Menstrual hygiene was better in urban than rural areas. It is imperative that adolescent girls be educated about the, significance of menstruation, and proper hygienic practices during menstruation. Sex education in school curriculum can help in resolving misconceptions about menstruation.